ANALISIS PEMBENTUKAN PORTOFOLIO SAHAM OPTIMAL SEKTOR PERTANIAN MENGGUNAKAN MODEL MARKOWITZ - Putra, Vicka Pramudya; Afrizal, Roni; Arnayulis, Arnayulis; Ariliusra, Azzukhruf (Smart Education, 2026)
Abstract: The purpose of this study to construct an optimal stock portfolio of companies in the agricultural sector listed on the Indonesia Stock Exchange (IDX) using the Markowitz portfolio model. This model is applied to optimize the trade-off between expected return and risk through the mean-variance framework. The data employed in this study consist of secondary data in the form of closing stock prices of six agricultural sector companies. The analytical procedures include the calculation of return, expected return, variance, standard deviation, covariance, and correlation among stocks, as well as the determination of optimal portfolio weights. The findings indicate that four stocks constitute the optimal portfolio, namely NSSS with a proportion of 57.79%, TAPG at 25.56%, SMAR at 11.55%, and STAA at 5.99%. The resulting optimal portfolio yields an expected return of 0.43% with a risk level of 0.01866, which is lower than the individual risk of each stock included in the optimal portfolio. These results demonstrate that diversification within agricultural sector stocks is effective in forming an efficient portfolio that achieves an optimal balance between risk and return. Keywords: Optimal Portfolio; Markowitz Model; Agriculture Sector Stock; Risk and Return. Abstrak: Penelitian ini bertujuan untuk membentuk portofolio saham optimal pada perusahaan sektor pertanian yang terdaftar di Bursa Efek Indonesia (IDX) menggunakan model portofolio Markowitz. Model ini digunakan untuk mengoptimalkan hubungan antara expected return dan risiko melalui pendekatan mean-variance. Data yang digunakan merupakan data sekunder berupa harga saham penutupan enam perusahaan sektor pertanian. Metode analisis meliputi perhitungan return, expected return, varians, standar deviasi, kovarians, dan korelasi antar saham, serta penentuan proporsi portofolio optimal. Hasil penelitian menunjukkan bahwa empat saham membentuk portofolio optimal, yaitu NSSS dengan proporsi 57,79%, TAPG sebesar 25,56%, SMAR sebesar 11,55%, dan STAA sebesar 5,99%. Portofolio optimal yang terbentuk menghasilkan expected return sebesar 0,43% dengan tingkat risiko sebesar 0,01866, dimana tingkat risiko tersebut di bawah risiko dari masing-masing saham individual pembentuk portofolio optimal. Hasil ini menunjukkan bahwa diversifikasi saham sektor pertanian mampu menghasilkan kombinasi portofolio yang efisien dengan tingkat risiko yang relatif rendah dan return yang optimal. Kata Kunci: Portofolio Optimal; Model Markowitz; Saham Sektor Pertanian; Risiko dan Return.